Properties of ceramic casting molds produced with two different binders - Saridikmen, H; Kuskonmaz, N (ELSEVIER SCI LTD, 2005)
In this study, a method for preventing the reaction between ceramic mold and stainless steel that occurs during the metal casting process has been introduced. The ceramic molds are produced using zircon ceramic powder with binders which are prepared with two different compositions, ethyl silicate [C8H20O4Si] and ethyl silicate/aluminum tri-sec-butoxide [Al(OCH(CH3)C2H5)(3)] solution. Hardness, porosity, sintering shrinkage, bulk density, surface morphology and chemical composition of the phases are examined. Stainless steel is poured into the ceramic mold and the mold-metal reaction behavior was examined in the cast product. Accordingly, burn-on casting defects encountered in stainless steel casting have exclusively been eliminated. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: ceramic mold; ethyl silicate; aluminum tri-sec-butoxide; Materials Science